
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


a) 10+2x=45:43
10+2x=42
10+2x=16
2x=16-10
2x=6
x=6:2
x=3
vậy x=3
b)130-(100+x)=25
100+x=130-25
100+x=105
x=105-100
x=5
vậy x=5
c)22.(x+32)-5=55
4.(x+9)=55+5
x+9=60:4
x+9=15
x=15-9
x=6
vậy x=9
d)72-7(13-x)=14
49-7(13-x)=14
7(13-x)=49-14
13-x=35:7
13-x=5
x=13-5
x=8
vậy x=8

a) x - 14 = 3x + 18
=> x - 3x = 18 + 14
=> -2x = 32
=> x = 32 : (-2)
=> x = -16
b) 2(x - 5) - 3(x - 4) = -6 + 15.(-3)
=> 2x - 10 - 3x + 12 = -6 - 45
=> -x + 2 = -51
=> -x = -51 - 2
=> -x = -53
=> x = 53
c) (x + 7)(x - 9) = 0
=> \(\orbr{\begin{cases}x+7=0\\x-9=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-7\\x=9\end{cases}}\)
Vậy ...
d) |2x - 5| - 7 = 22
=> |2x - 5| = 22 + 7
=> |2x - 5| = 29
=> \(\orbr{\begin{cases}2x-5=29\\2x-5=-29\end{cases}}\)
=> \(\orbr{\begin{cases}2x=34\\2x=-24\end{cases}}\)
=> \(\orbr{\begin{cases}x=17\\x=-12\end{cases}}\)
Vậy ...

- a\(x-14=3x+18\Rightarrow3x-x=-14-18=-32\Rightarrow x=-16\)
- b, \(2\left(x-5\right)-3\left(x-4\right)=-6+15.\left(-3\right)\Rightarrow2x-10-3x+12=-6-45\)
- \(\Rightarrow-x+2=-51\Rightarrow-x=-53\Rightarrow x=53\)
- c.\(\left(x+7\right).\left(x-9\right)=0\Rightarrow\orbr{\begin{cases}x+7=0\\x-9=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-7\\x=9\end{cases}}}\)
- d.Bạn tự làm nhé
d) \(\left|2x-5\right|-7=22\)
\(\Rightarrow\left|2x-5\right|=22+7\)
\(\Rightarrow\left|2x-5\right|=29\)
\(\Rightarrow\orbr{\begin{cases}2x-5=29\\2x-5=-29\end{cases}}\) \(\Rightarrow\orbr{\begin{cases}2x=34\\2x=-24\end{cases}}\) \(\Rightarrow\orbr{\begin{cases}x=17\\x=-12\end{cases}}\)
Vậy x = 17 hoặc x = -12

\(\left(-3x+2\right)-\left(5-3x\right)=-3\)
\(\Rightarrow-3x+2-5+3x=-3\)
\(\Rightarrow-3x+3x=-3+5-2\)
\(\Rightarrow0x=0\Rightarrow x\in Z\)
\(3+x-\left(3x-1\right)=6-2x\)
\(\Rightarrow3+x-3x+1=6-2x\)
\(\Rightarrow x-3x+2x=6-1-3\)
\(\Rightarrow0x=2\left(loại\right)\)
\(\left(x-5\right)\left(3x+4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\3x+4=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=-\frac{4}{3}\end{cases}}}\)
\(7x\left(2x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}7x=0\\2x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{2}\end{cases}}}\)
\(\left(3x-1\right)2x=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x-1=0\\2x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=0\end{cases}}}\)

1) 14x-8x=10+5
x(14-8)=15
x6=15
x=15/6
2)5x-3x=30-15
2x=15
x=15/2
3)làm tương tự

a) 3x - 4 = -2x + 5
<=> 3x = -3x + 9
<=> 3x + 2x = 9
<=> 5x = 9
<=> x = 9/5
\(\text{a) 3x-4=-2x+5}\)
\(3x-4=-2x+5\)
\(3x+2x=5+4\)
\(5x=9\)
\(\Rightarrow x=\frac{9}{5}\)
\(\text{b) 3(-4-2x) =3x+6}\)
\(-12-6x=3x+6\)
\(-6x-3x=6+12\)
\(-9x=18\)
\(\Rightarrow x=-2\)
\(\text{c) /3x-2/=2x-1}\)
\(\Rightarrow\orbr{\begin{cases}3x-2=2x-1\\3x-2=-\left(2x-1\right)\end{cases}\Leftrightarrow\orbr{\begin{cases}3x-2=2x-1\\3x-2=-2x+1\end{cases}}}\)
\(\Leftrightarrow\orbr{\begin{cases}3x-2x=-1+2\\3x+2x=1+2\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\5x=3\end{cases}}}\)\(\Leftrightarrow x\in\left\{1;\frac{3}{5}\right\}\)
học tốt
3/2x - 2/3 x = -4/15 + 2/5
5/6x = 2/15
x = 2/15 : 5/6
x = 4/25